A comparative evaluation of a new generation jail - Williams, James L. (American journal of criminal justice, 1999)
This study reports findings from an evaluation of a new generation jail in a large southwestern state. The jail is one component of a complex containing a traditional jail, an indirect supervision facility (barracks), and the new generation jail. Using survey and operational data, we compare the new generation jail to the other two facilities. The findings provide generally positive support for the effectiveness of the new generation jail. Inmates and staff were much more satisfied with the physical facilities. Staff perceived it as more secure, though they reported only limited advantages in safety and security. Violence and disciplinary problems were substantially lower. However, no savings in staffing levels were noted, nor were there differences in job satisfaction for staff in the new generation jail. We discuss the implications of the findings and suggest additional directions for jail evaluations.